THE EFFECT OF STRATEGIC ADVERTISING ON CONSUMER BRAND LOYALTY: A CASE OF BRITAM ASSET MANAGERS LIMITED, NAIROBI, KENYA - Mallowah, Sheila; Maswili, Richard (Journal of Strategic Management, 2017)
Abstract Purpose: The purpose of the study was to establish the effect of strategic advertising on consumer brand loyalty. Methodology: The study used the descriptive research design. The population of this study comprised of a total of 6,500 Britam Asset Managers Limited customers. The target population comprised all of Britam Asset Managers Limited customers within Nairobi. The sample size of this study was 357 respondents. Both Stratified sampling and random sampling techniques were used to select the sample. The primary data was collected through questionnaires. The data collected was then subjected to both quantitative and qualitative analysis. The findings of the research study were presented using appropriate graphs, frequency tables and charts. Statistical Packages for Social Sciences (SPSS) was used. Results: The findings showed that, strategic advertising created awareness of the company's products and services, it also assured customer of the safety of their investments with the company and finally convinced customers to continue using products and services. The study also identified factor that affect customer brand loyalty which included; high quality perception of the, company's products and services, popularity of the firm's brand name, firm's experience in the financial service industry, the experience of the company's key staff members among others. Further, the results in indicate that strategic advertising had a positive significant association with consumer brand loyalty. Unique contribution to theory, practice and policy: The study recommended that companies need to position their brands in the minds of consumers in order to achieve desired goals of their strategic advertising. The study also recommended that companies have to break the clutter by evolving innovative ways to attract the attention of the target audience and boost their customer's loyalty.